Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-74326-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high fat diet and excessive compressive mechanical force on pathologic changes of temporomandibular joint

Abstract: The aim of this study was to investigate the effect of high fat diet and excessive compressive mechanical force on temporomandibular joint. In vivo, a mouse model of temporomandibular joint compressive loading device was used. A high fat diet mouse model and a combined mouse model intraperitoneally treated with or without simvastatin were used in the study. The pathological changes of mandibular condylar cartilage were assessed by Safranin-O staining. The IL-1β, MMP-3, leptin expression changes in the cartilag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Logistic regression analysis showed no significant association between BMI and the presence of OA, and it suggested that the rs8044769 variant is significantly associated with TMJOA. However, results of an in vivo mouse model suggested that the development of pathological changes in TMJ could be caused by the excessive compressive mechanical force and high-fat diet-induced obesity [ 29 ]. In addition, it has been reported that a quick eating rate is positively associated with excess body weight [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression analysis showed no significant association between BMI and the presence of OA, and it suggested that the rs8044769 variant is significantly associated with TMJOA. However, results of an in vivo mouse model suggested that the development of pathological changes in TMJ could be caused by the excessive compressive mechanical force and high-fat diet-induced obesity [ 29 ]. In addition, it has been reported that a quick eating rate is positively associated with excess body weight [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association of osteoarthritis histological severity and lipid accumulation in cartilage was reported [32][33][34]. In a TMJ OA study, the degeneration of the joint was associated with mechanical overload and high-fat diet [35].…”
Section: ) Obesity and Adipose Tissuementioning
confidence: 96%
“… Griffin et al (2010) first observed loss of proteoglycans in the TMJ of C57BL/6J mice with a high-fat diet (45% kcal fat) for 45 weeks. Du et al (2020) studied the effect of high-fat diet (60% kcal fat) on TMJ of C57BL/6 mice. Less cartilage matrix, thinner condylar cartilage, and vertical clefts were observed in overweight mice after 12 weeks of high-fat feeding.…”
Section: Classification Of Animal Models In Temporomandibular Joint O...mentioning
confidence: 99%